2007
DOI: 10.1007/s10840-007-9158-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the maximum voltage-guided technique for cavotricuspid isthmus ablation during ongoing atrial flutter

Abstract: (1) The major finding of this study is that MVGT is a feasible method even during ongoing atrial flutter. (2) Our data confirm that MVGT is an effective technique for CTI ablation with considerable decrease in procedure and fluoroscopy times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
3
14
2
Order By: Relevance
“…By targeting high‐amplitude signals along the CTI, one can produce bidirectional block more rapidly than by creating a contiguous line of lesions across the CTI 6,10,11 . Consistent with the findings of previous single‐center studies, 7,9 voltage‐guided ablation in this study substantially reduced ablation requirements, including fluoroscopy exposure and procedure duration. By contrast, the only multicenter study on voltage‐guided CTI ablation published so far applied strict rules for remapping the isthmus before each voltage‐guided ablation lesion.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…By targeting high‐amplitude signals along the CTI, one can produce bidirectional block more rapidly than by creating a contiguous line of lesions across the CTI 6,10,11 . Consistent with the findings of previous single‐center studies, 7,9 voltage‐guided ablation in this study substantially reduced ablation requirements, including fluoroscopy exposure and procedure duration. By contrast, the only multicenter study on voltage‐guided CTI ablation published so far applied strict rules for remapping the isthmus before each voltage‐guided ablation lesion.…”
Section: Discussionsupporting
confidence: 84%
“…So far, there have been no concerns that MVG ablation may compromise the long‐term ablation success 7,8,11 . Although we did not follow our study patients in the long term, other authors reported on a reasonably low‐AFL recurrence rate of 3.9% over an average of 21 months after voltage‐guided CTI ablation 11 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additional evidence supporting conduction over bundles comes from reports of bidirectional CTI block obtained with single ablation lesions over a single predominant voltage 8,9 . The MVG approach has also been validated when ablation is performed during ongoing CTI‐dependent atrial flutter, again suggesting reduced procedure, ablation, and fluoroscopy time 10 …”
Section: Evidence Of Conduction Over Bundlesmentioning
confidence: 96%
“…Often referred to as maximum voltage‐guided ablation of atrial flutter, the benefits of this technique have since been suggested by small prospective, randomized trials in which this technique was compared with the traditional anatomically‐based, continuous “drag” method. In trials ranging from 20 to 69 patients in size, the maximum voltage‐guided technique was associated with shorter procedure times, 10 shorter ablation times, 11,12 shorter fluoroscopy times, 10,12 and fewer ablation lesions 10–12 . Long‐term outcomes from this technique are not yet available.…”
Section: Editorial Commentmentioning
confidence: 99%